2017
DOI: 10.1039/c7ra03367b
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study on intrinsic defects of SnSe

Abstract: Sn vacancies can work as an effective source for p-type conduction under both Sn- and Se-rich conditions while n-type conduction is unlikely to be realized due to the absence of the effective intrinsic source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 54 publications
9
47
0
Order By: Relevance
“…From a full geometry relaxation, the lattice constants of SnSe were predicted at a = 11.571 Å, b = 4.168 Å and c = 4.517 Å, which are in good agreement with the experimental values (a = 11.550, b = 4.153, and c = 4.450 Å). The optimized of Sn-Se bond lengths were calculated to be 2.78 and 2.83 Å, which also agree well earlier theoretical prediction 48 . The SnSe (100), (001), (011), and (111) surfaces surface were created from the optimized bulk material using the METADISE code 49 , which ensures the creation of surfaces with zero dipole moment perpendicular to the surface plane 50 .…”
Section: Resultssupporting
confidence: 89%
“…From a full geometry relaxation, the lattice constants of SnSe were predicted at a = 11.571 Å, b = 4.168 Å and c = 4.517 Å, which are in good agreement with the experimental values (a = 11.550, b = 4.153, and c = 4.450 Å). The optimized of Sn-Se bond lengths were calculated to be 2.78 and 2.83 Å, which also agree well earlier theoretical prediction 48 . The SnSe (100), (001), (011), and (111) surfaces surface were created from the optimized bulk material using the METADISE code 49 , which ensures the creation of surfaces with zero dipole moment perpendicular to the surface plane 50 .…”
Section: Resultssupporting
confidence: 89%
“…[40] The films exhibit Seebeck coefficients of a similar magnitude to those seen by Zhao et al at room temperature. [13] While in single-crystal SnSe, the Seebeck coefficient is seen to drop from ≈550 to ≈350 µV K −1 between 600 and 800 K, [13] for thermally evaporated thin films, the Seebeck coefficient is >600 µV K −1 at room temperature, but drops to ≈140 µV K −1 by 600 K with the drop starting at 460 K. This drop is more pronounced and at lower temperatures compared to single-crystal SnSe.…”
Section: Thermoelectricssupporting
confidence: 67%
“…Based on the DFT calculations, it has been reported that both V Se and V Sn + 2V Se produce only localized electrons and do not contribute to band transport in SnSe [24]. While V Se can behave as both a donor and an acceptor depending on the Fermi level [23], the complex defects (V Sn + nV Se ) tend to be acceptors. This is indicated by the transport measurements (increase in the hole concentration) presented in Sec.…”
Section: A Positron Annihilation Spectroscopymentioning
confidence: 99%
“…Recently, more particular attention has been given to intrinsic defects (IDs) [15,[21][22][23]. The intrinsic defects, e.g., Sn vacancies (V Sn ), seem to play a very important role in the excellent electronic properties of SnSe at elevated temperatures [15,24].…”
Section: Introductionmentioning
confidence: 99%